PENGARUH REKRUTMEN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PALOPO - Riska Wulandari; Muhammad Kasran; Suparni Sampetan (Universitas Bina Taruna Gorontalo, 2023)
This study aimz to analyze taken using the accidental sampling method with a total of 115 respondents. Data were analyzed using a quantitative appoarch through Multiple Regression Analysis using the SPSS Aplication. Based on this research, the results of determining recruitment have no effect on employee performance. Work Placement effects Employee Performance. Recruitment and Work Placement have a positive and simultaneous effect on Employee Performance.